2018
DOI: 10.3126/bjhs.v2i3.18946
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stigma towards Mental Illness among College Students of Western Nepal

Abstract: Introduction: Stigma of people towards mental illness is still prevailing in our country due to lack of awareness. General public's view about mental illness remains largely unfavourable. The topic of mental illness itself evokes a feeling of fear, embarrassment or even disgust fostering negative attitudes towards mental illness and mentally ill people. There is paucity of articles on this topic from our country.Objective: To investigate college students' stigma towards mental illness and factors associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The study population included conveniently sampled students attending in classes 11,12 of Delhi Public School after a written consent from both the principal and the participants.The sample size was calculated with 95% confidence interval and 80% power. Taking into consideration a similar study done in western Nepal among college students (Pokharel B, Pokharel A), 7 the level of stigma towards mental illness was 43.6%. Considering this the negative attitude towards mental illness the sample size was calculated with prevalence as 43.6, compliment of prevalence 56.4 and permissible error at 20% as 8.72.…”
Section: Methodsmentioning
confidence: 80%
See 2 more Smart Citations
“…The study population included conveniently sampled students attending in classes 11,12 of Delhi Public School after a written consent from both the principal and the participants.The sample size was calculated with 95% confidence interval and 80% power. Taking into consideration a similar study done in western Nepal among college students (Pokharel B, Pokharel A), 7 the level of stigma towards mental illness was 43.6%. Considering this the negative attitude towards mental illness the sample size was calculated with prevalence as 43.6, compliment of prevalence 56.4 and permissible error at 20% as 8.72.…”
Section: Methodsmentioning
confidence: 80%
“…None of the factors among gender, urban or rural background, history of mental illness, relative or friend with mental illness alone were significantly related to the level of perceived stigma among the college students during their graduation studies which was similar to our findings. 7 Researches done in neighboring countries like Pakistan showed no differences in attitude between males and females. 13 However, in our study males were found to have more negative attitude than the females.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Pharmacy student reported more negative attitudes and stigma than other medical and science undergraduate university students ( Shehata and Abdeldaim, 2020 ). Furthermore, about 43.6% of the student at science college reported stigma toward patient with mental illness ( Pokharel and Pokharel, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nepal is not an exception towards stigma for mental illness, where, public stigma towards mental illness was 43.6% [15]. Public stigma was measured using devaluation discrimination scale developed by Link and colleagues.…”
Section: Introductionmentioning
confidence: 99%